Plant Survival in a Changing Environment: The Role of Nitric Oxide in Plant Responses to Abiotic Stress - Simontacchi, Marcela; Galatro, Andrea; Ramos-Artuso, Facundo; Santa-María, Guillermo E. (Frontiers in Plant Science, 2015)
Nitric oxide in plants may originate endogenously or come from surrounding atmosphere and soil. Interestingly, this gaseous free radical is far from having a constant level and varies greatly among tissues depending on a given plant´s ontogeny and environmental fluctuations. Proper plant growth, vegetative development, and reproduction require the integration of plant hormonal activity with the antioxidant network, as well as the maintenance of concentration of reactive oxygen and nitrogen species within a narrow range. Plants are frequently faced with abiotic stress conditions such as low nutrient availability, salinity, drought, high ultraviolet (UV) radiation and extreme temperatures, which can influence developmental processes and lead to growth restriction making adaptive responses the plant´s priority. The ability of plants to respond and survive under environmental-stress conditions involves sensing and signalling events where nitric oxide becomes a critical component mediating hormonal actions, interacting with reactive oxygen species, and modulating gene expression and protein activity. This review focuses on the current knowledge of the role of nitric oxide in adaptive plant responses to some specific abiotic stress conditions, particularly low mineral nutrient supply, drought, salinity and high UV-B radiation.